Diagnosis of broad complex tachycardias with ambulatory monitoring of atrial electrography. Issue 6432 (9th June 1984) - Lipkin, D P; Perrins, E J; Shapiro, L M; Ludgate, L; Fox, K M
Abstract : Simultaneous 24 hour ambulatory monitoring of the surface electrocardiogram and the intra-atrial electrocardiogram was evaluated in eight patients with broad complex tachycardia. The technique using a J shaped atrial pacing wire permitted a distinction between ventricular tachycardia and supraventricular tachycardia in all eight patients. Formal electrophysiological testing would still be required, however, in patients in whom diagnostic doubt remained.